Meme-Assisted Debate: 21st Century Visuals Serving EFL Spoken Production on a Sample of Level B2 Hungarian Secondary School Students - Kocsis, Andrea (AMERICANA E-journal of American Studies in Hungary, 2024)
The aim of the present research is to introduce and assess the application of thematically structured internet macros as a starting point for a level B2 EFL debate task on national stereotypes related to the culture and everyday life of the United States of America. The main focuses of the paper include attempts at describing how and why such 21st century visuals can be loaded with the capacity of enhancing L2 oral production and examining students’ self-reflections and (self-)evaluations of the learning outcome. Also, it gives some interesting research-based insights into the characteristic features of the typical present day teenage language learner in the system of Hungarian public education with relevance to the methodology of teaching foreign languages.